KEY CONCEPTS OF TOURISM PROMOTED IN BANDUNG AND PANGANDARAN TOURISM WEBSITES - Arien Arianti Gunawan, - (2011)
This research entitled Key Concepts of Tourism in Bandung and Pangandaran Tourism Website examines the key concepts of tourism and the presentation of the concepts in Bandung and Pangandaran tourism websites. The data used in this research are in the form of websites which consist of words, phrases, sentences, as well as the design and technical performance of the websites. The websites selected are those written in English and most favorite tourism sites as judged by 100 respondents involved in the research. Both websites are analyzed using Leximancer to investigate the key concepts of tourism in the websites. Checklist of requirements of a tourism website proposed by Briggs (2001) has been applied to identify how the concepts are presented in the websites. The research found that key concepts offered by Bandung tourism websites are Bandung, home, tourism, events, and accommodation. These key concepts emphasize the homey atmosphere of the city. On the other hand, Pangandaran emphasizes the names of their tourism objects by presenting key concepts such as Green Canyon, Batu Karas, and National Park. In terms of technical requirements, both websites have fulfilled the requirements of clear navigations and ease of use. However, some important features, i.e. interactive feature, security of personal information, regular updates, online bookings, and photo collections are missing. Overall, the presentation of both websites appear to be too simple and less interesting, as they use less persuasive language and less attractive design. It is suggested that future studies use more tourism websites and compare them with tourism websites in other countries for more comprehensive results. It is also suggested that tourism marketers are willing to re-evaluate their tourism websites to make them more attractive, accessible, and informative to potential tourists.